Women in the Sky : Gender and Labor in the Making of Modern Korea - Nam, Hwasook, 1959- (Book collections on Project MUSE., 2021)
"This book examines Korean women factory workers' century-long activism from the 1920s to the present in broad historical context with a focus on gender politics in the labor movement and in the larger society"--